Role of Various Pre Operative Risk Factors in Outcome Following Coronary Artery Bypass Graft: An Institutional Based Study - Yadav, Lokesh; Sharma, Praman (Journal of National Heart and Lung Society Nepal, 2022)
Background: Coronary Artery Bypass Graft (CABG) is done in patient with Coronary Artery Disease (CAD) with Normal or decreased Left Ventricular Ejection Fraction (LVEF). Most of the patient with CAD presents with NYHA class II or III.Methods: It’s an analytical study of retrospectively collected data of all patients who underwent CABG for CAD. Data were collected over the period of about 30 months at Nobel Medical College and Teaching Hospital.Results: There were a total of 54 patients in our study. There was male 38 (72%) predominance. There were 49 (92.5%) cases having BMI